Assessing the Mediating Role of Depression in the Relationship Between Feeling of Loneliness and Social Functioning in the Elderly - Roya Zakizadeh; Masoud Bahreini; Akram Farhadi; Razieh Bagherzadeh (University of Social Welfare & Rehabilitation Sciences, 2023)
Objectives: Due to the rapid growth of the elderly population, it is very important to pay attention to their mental health indicators including feeling of loneliness, social functions and depression. This study aims to determine the mediating role of depression in the relationship between feeling of loneliness and social functioning in the elderly. Methods & Materials: In this correlational cross-sectional study, 318 older adults covered by the comprehensive health centers in Bushehr, south of Iran in 2018 were selected using a simple random sampling method. To collect data, Russell's UCLA loneliness scale (version 3), and Goldberg's general health questionnaire (Depression and social dysfunction subscales) were used. We applied the partial least squares-structural equation modeling to analyze the data in PLS Graph version 3.00 software. The significance level was set at 0.05. Results: The mean age of the participants was 66.74±5.87 years; 55.3% were male and the rest were female. The results showed that feeling of loneliness directly (β=0.199, P<0.01) and through mediation by depression (β=0.183, P<0.001) could cause social dysfunction. Felling of loneliness and depression together explained 20% of the variance in social dysfunction. The outer and inner model fit indices indicated the models' good fit. Conclusion: Feeling of loneliness directly or by causing depression can reduce the social functioning of the elderly. The results of this study can be used in designing effective interventions to increase the social functioning of the elderly.